BRAND IMAGE AND PRICE AGAINST CONSUMER PURCHASE DECISION ON KARAWANG GACOAN MIE - Muhammad Maghribi Badau; Farida Anum; Eman Sulaeman (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2023)
The purpose of this study was to determine and analyze the effect of brand image and price on purchasing decisions at Mie Gacoan Karawang. The approach used in this study is an associative approach. The method used in this research is quantitative. The population used was all consumers who had purchased Mie Gacoan Karawang, and the sample used was all consumers who filled out Google from, a total of 54 people. The data analysis technique in this study is Multiple Linear Analysis, Classical Assumption Test, F Test and t Test, and Coefficient of Determination Test. The results showed that partially and simultaneously Bran Image and Price had a significant effect on consumers' purchasing decisions of Mie Gacoan Karawang.